Questões sobre soja e imperialismo na Revista Brasiliense - Marques, Vicente Penteado Meirelles de Azevedo (2023)
The essay aims to analyze the relations established between soybean cultivation and processing and the development process in Brazil and other countries. Authors and articles published in Revista Brasiliense in the period from 1955 to 1964 were selected, a periodical representative of a nationalist and leftist project for Brazil. The national and international political scenarios and soybean cultivation in Brazil and abroad during the magazine's existence and after its end were characterized. The results show relevant contributions to the understanding of different dimensions of food and power relations between countries today.